Correction to: Analysis of food and fluid intake in elite ultra-endurance runners during a 24-h world championship - Chloé Lavoué; Julien Siracusa; Émeric Chalchat; Cyprien Bourrilhon; Keyne Charlot (Taylor & Francis Group, 2021)
An amendment to this paper has been published and can be accessed via the original article.